(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-3-163-171 There is a relevant problem of the development and formation of linguistic and cultural competence. The teaching of foreign students with the help of country-oriented material, the use of which makes it possible to overcome the problems of intercultural communication, is becoming increasingly important. In this regard, the article presents the implementation of the national-regional component in teaching Russian to foreign students on a project basis. The relevance of the work consists in the study of the project method and the development of a specific methodology. The purpose of the research is to show how the application of this method develops and forms professional communication skills and linguistic and cultural competence of students. The novelty of the research is connected with the development of professional projects, taking into account regional specifics, containing lexical comments and a system of exercises for developing communicative, lexical and grammatical skills. This work allows to make a conclusion that prospects of the project method in the process of teaching RFL took place as well as the feasibility of developing a learning strategy based on projects of linguistic and cultural topics in teaching RFL. The use of regional materials provides a meaningful basis and creates situational professional communication as well as contributes to the formation of linguistic and cultural competence of foreign students; it integrates the regional knowledge from the other subject areas, prepares for international professional communication. Key words: foreign students, methods of RFL teaching, project method, regional component, communicative exercises, linguoculturology, linguistic and cultural competence, linguistic and cultural information.